Effective recruitment strategies in an exercise trial for patients with fibromyalgia. - Park, Michelle.; Bannuru, Raveendhara R.; Price, Lori Lyn.; Harvey, William F.; Driban, Jeffrey B.; Wang, Chenchen. (Tufts University. Tisch Library., 2021)
Keywords: Fibromyalgia, Recruitment, Chronic pain, Pain management, Complementary and integrative health, Exercise trial.; Springer Open.